Cost Benefits of Photobathymetry - Collins, James (The International Hydrographic Review, 2015)
The National Ocean Survey has recently completed photographing approximately 60 square nautical miles of underwater area surrounding St. Croix Island, Virgin. Islands. Analysis of the field, data acquisition, and processing costs for this underwater mapping project show that photobathymetry is a cost-effective surveying technique. A comparison between photogrammetric underwater mapping and conventional launch hydrography gives a cost benefit ratio of 6:1 in favor of bathymetry.